Indigenous Peoples: Traditional knowledges, climate change, and health. - Nicole Redvers; Paula Aubrey; Yuria Celidwen; Kyle Hill (Public Library of Science (PLoS), 2023)
Indigenous Peoples around the globe make up approximately six percent of the global population, yet they sustainably care for around eighty percent of the world's remaining biodiversity. Despite continued political, economic, and racial marginalization, as well as some of the worst health inequities on the planet, Indigenous Peoples have worked hard to maintain their cultures and languages against all odds. Indigenous Peoples' close connections to land, water, and ecosystems, however, have placed them at increasing vulnerability from the effects of climate change. With this, the health risks from climate change have unique considerations within Indigenous Nations for both mitigation and adaptation responses that are largely unappreciated. This Indigenous narrative review will synthesis the current climate and health landscape of Indigenous Peoples at a global, high-level scale, including relevant international mechanisms and considerations for Indigenous Peoples' health. This Indigenous narrative review will also explore and reflect on the strengths of Indigenous traditional knowledges as it pertains to climate change and health.